AKTIVITAS BELAJAR MURID PADA PEMBELAJARAN PKn DENGAN MENGGUNAKAN TEKNIK NUMBERED HEAD TOGETHER DI KELAS II SEKOLAH DASAR - Nuryanti, Eni; Utami, Sri; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe improvement of student Learning Activity on Civics subject Learning by using Numbered Head Techniques in Class II of SD Negeri 32 Pontianak Tenggara. The aim is to improve student learning activities in PKn. The reasearch is Classroom Action Research, The subject is the classroom teacher and class II student consist of 23 people. Technique of collecting data is direct observation , the tool of data collection is observation sheet. This research was conducted in 3 cycles. The results of the study were the ability of the teacher to plan learning 3.58, in cycle 1 and 4.00 in cycle 3, the ability of the teacher to carry out learning 3.57 cycle 1 and 4.00 in cycle 3, physical activity 44.92% in the first cycle with the category